Problematika Guru Dalam Pembelajaran Ipa Pada Kurikulum Merdeka - Amalia, Ema Nur; Ramadhani, Putriana; Rosanti, Aulia Yunita; Parsha, Azzahra Salmanabila; Khoirunnisa; Budiono, Hendra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the challenges faced by teachers in teaching Natural Sciences (IPA) within the implementation of the Kurikulum Merdeka at the elementary school level. Using a qualitative approach with a case study design, data were collected through in-depth interviews, classroom observations, and document analysis. The subject of this study was a classroom teacher at SDN 112/I Perumnas who had applied the Kurikulum Merdeka in her teaching practice. The findings revealed seven key themes: limited availability of learning media, time and logistical constraints, teacher creativity in overcoming resource limitations, varied teaching methods, application of Problem-Based Learning and Project-Based Learning approaches, the adequacy yet suboptimal use of learning facilities, and the gradual adaptation process to the new curriculum. These findings indicate that while teachers have made efforts to implement active and contextual learning, significant challenges remain, both technical and systemic. Therefore, continuous support is needed in the form of training, provision of instructional media, and policies that promote teacher flexibility and creativity in effectively implementing the curriculum.